2013
DOI: 10.1103/physreva.88.042501
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic effects on the hyperfine structures of2p4(3P)3p2Do,<

Abstract: The hyperfine interaction constants of the 2p 4 ( 3 P )3p 2 D o 3/2,5/2 , 4 D o 1/2−7/2 and 4 P o 1/2−5/2 levels in neutral fluorine are investigated theoretically. Large-scale calculations are carried out using the multiconfiguration Hartree-Fock (MCHF) and Dirac-Hartree-Fock (MCDHF) methods. In the framework of the MCHF approach, the relativistic effects are taken into account in the Breit-Pauli approximation using non relativistic orbitals. In the fully relativistic approach, the orbitals are optimized usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…The overall consistency between the so-deduced corrections, in particular in the cases where they account for a large fraction of the hyperfine constants, brings a new evidence that they yield useful estimates of relativistic effects. This is particularly interesting in the context of non-relativistic methods, as it is in general necessary to consider the impact of relativity on the results [33]. Tables IV, V and VI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall consistency between the so-deduced corrections, in particular in the cases where they account for a large fraction of the hyperfine constants, brings a new evidence that they yield useful estimates of relativistic effects. This is particularly interesting in the context of non-relativistic methods, as it is in general necessary to consider the impact of relativity on the results [33]. Tables IV, V and VI.…”
Section: Discussionmentioning
confidence: 99%
“…We compare the Breit-Pauli Configuration Interaction method (BPCI) [30], and the Relativistic configuration interaction method using the Pauli approximation (RCI-P) [34]. Such a comparison has recently been performed for excited states of fluorine [33], showing a good consistency between the two approaches. For differential effects like the electron affinity and its isotope shift, one has to strike a balance in the nonrelativistic approach as well as in the relativistic one.…”
Section: E Relativistic Correctionsmentioning
confidence: 99%
“…Predictions can be improved with expansions that take into account the atomic property under investigation. Applications that have been extensively investigated are spectrum calculations for all levels up to a designated excited level, allowed and forbidden transitions [143,148,197,198,54], isotope shifts [199,200,201,184,202,203], hyperfine structures [204,159,205,206], nuclear effects on transition rates and spectra [26,207], magnetic field-induced transitions [208,209,20], to name a few. A comprehensive list of relativistic calculations and theoretical studies can be found in the RTAM bibliography database [210].…”
Section: Discussionmentioning
confidence: 99%
“…This method, based on the use of a relativistic configuration interaction approach in the Pauli approximation, labelled RCI-P, provides an interesting way of checking the reliability of independent MCHF-BP calculations [153,159].…”
Section: Nonrelativistic Mchf Orbitals With a Relativistic Hamiltonianmentioning
confidence: 99%
“…In the present contribution, we illustrate how relativistic corrections can be large in fluorine, despite its low atomic number (Z = 9). Table 1 reports the theoretical values of the magnetic dipole hyperfine constant A J for 2p 4 3p that are estimated using elaborate single-and double-multireference MCHF correlation models [23], together with the experimental value [158] for 2 D 5/2 o . The calculations are performed using the multiconfiguration Hartree-Fock (MCHF) and DiracFock (MCDF) methods.…”
Section: Relativistic Effects In Light Elementsmentioning
confidence: 99%